Crystalline Bi2Se3 topological insulator films prepared by dc magnetron sputtering. (July 2020) - Kumar, R.; Yadav, A.K.; Biswas, A.; Nand, Mangla; Bahadur, J.; Ghosh, S.; Jha, S.N.; Bhattacharyya, D.
Abstract: Topological insulator thin films of Bi2 Se3 have been deposited on SrTiO3 (111) substrate by dc magnetron sputtering and annealed in Se environment. X-ray Diffraction (XRD) measurement shows (00 l ) ( l = 3n, where n is an integer) type of reflections over 2θ range of 10–80° without any other peaks indicating that the films are of single crystalline quality along the [001] growth direction confirming that highly c-axis-preferred orientated Bi2 Se3 thin films can be obtained by relatively simpler and easily scalable dc magnetron sputtering technique. The results are also confirmed by Field Emission Scanning Electron Microscopy (FESEM), Energy Dispersive X-ray Spectroscopy (EDXS), Photo-electron Spectroscopy (PES) and X-ray absorption spectroscopy (XAS) measurements. Highlights: Bi2 Se3 films have been prepared on SrTiO3 substrates by dc magnetron sputtering. Films prepared at higher substrate temperature followed by annealing under Se ambient. As-deposited and annealed films were characterized by XRD, XAS and PES. Annealed samples show perfect stiochiometry and better c-axis orientation. Annealed samples show enhanced presence of states near Fermi edge.